Analisis Manajemen Pembiayaan Murobahah BMT - Ryski Pebriana; Rofik Efendi (WADIAH, 2019)
The development of Islamic banking and Islamic financial institutions in Indonesia lately increasing. One reason is the strong belief in the Muslim community that banking and conventional financial institutions contain usury which is prohibited by Islam. The presence of Agritama Srengat Blitar BMT as Syari'ah savings and loans is intended to be a more innovative alternative in financial services, the financing process is also not complicated. The absence of an element of usury to Murabahah financing, and the ease of the process and conditions for financing, does not make more and more bad loans. The approach used in this research is a qualitative descriptive approach, while the type of research is field research, and the method of collecting data is observation, interview and documentation, which is using three steps, data reduction, file presentation and drawing conclusions.The results of this study indicate that: 1). Financing procedures at BMT Agritama Srengat Blitar use 5C analysis (character, capacity, capital, collateral, condition) and take into account a maximum radius of 10 km, but this does not apply to existing customers and customers who get recommendations from partners. 2). The implementation of Murabahah financing management has not been in accordance with the murabaha management function which includes planning, organizing, implementing, and controlling. Where the planning of murabahah financing is devoted to agriculture and animal husbandry, but in practice it is not appropriate, then in the implementation of murabahah financing using a wakalah contract it is signed together with murabahah. And the supervision conducted by BMT Agritama is not routinely visited to the place of business.